Quantification des niveaux d`activité électromyographique des muscles agonistes et antagonistes lors de contractions musculaires isométriques, concentriques et excentriques - Colson, S. S. (Movement & Sport Sciences - Science & Motricité, 2014)
In human movement sciences, the introduction and development of isokinetic dynamometers made the assessment of muscle torque produced during isometric, concentric and eccentric single-joint movements easier. However, the concomitant recording of the electrical activity of agonist and antagonist muscles involved in the movement by surface electromyography (sEMG) remains untapped. Although many methodological precautions must be taken during the recording and analysis of sEMG signals, this method provides information regarding the neural drive that is relevant in sport sciences, ergonomics, as well as physical medicine. This article gives an overview of normalization methods of sEMG signals and their respective influence upon the sEMG-angle and sEMG angular-velocity relationships of agonist and antagonist muscles during torque production.